Bioprocessing of mAb (Monoclonal Antibodies) using Chinese Hamster Ovary (CHO) Cells: A Review - Josefano, Richelle Bertly; A, Aivyanca; Dungus, Charlivo Mikaichi; Hamid, Jason Jonathan; Katherine, Katherine (Indonesia International Institute for Life Sciences, 2023)
Monoclonal antibodies (mAb) are known to be able to be produced from Chinese Hamster Ovary (CHO) cells. It has become increasingly important throughout the years due to its efficiency and revolutionary treatment for various diseases such as cancer, autoimmune diseases, and so forth. This review examines several upstream and downstream processes involved in the production of mAb including CHO cell maintenance, cellular engineering of CHO, transfection of plasmids into CHO cells, clonal selection and screening, culture of rCHO cells, cell harvesting, purification, and polishing. Several challenges of the bioprocessing process include a lack of large up scaling for industrial purposes, high capital costs, as well as productivity inefficiencies. However, a solution proposed is for biopharmaceutical companies to research further into the downstream processing for a continuous, efficient, and productive process.